The Figure of the Worker and the Figure of the Migrant: From the 1984-85 Miners’ Strike to the ‘Channel Migrant Crisis’ in Kent - Jemima Parker (Revue Française de Civilisation Britannique)
The paper argues that the decline of the figure of the worker within British politics following upon the Miners’ Strike of 1984-85 can be profitably viewed in relation to a concomitant renewed emphasis on immigration and the figure of the migrant in political discourse through the replacement of the post-war social democratic consensus with a narrowly inscribed vision of the nation.